(untitled) (Educação e Pesquisa, 2005)
The present work analyzes the representations of teaching publicized by the pedagogic press at the Imperial Court between the 1870s and the 1880s, taking as the basis for its documental research articles published by primary teachers in the journal Instrução Pública (Public Instruction). The text also wants to reveal how, through this process of construction and re-elaboration of representations and identities, the teachers presented themselves to the readers as a professional category, sometimes directly, as in the personal examples and trajectories they analyzed, some-times through various issues, when they dealt with social and educational problems they regarded as fundamental. The pedagogical press is a privileged instrument to understand the workings of the educational field. In that journal we can find information and representations about the teaching profession, the pedagogical practices, and the demands of the teaching professional category. It is thus possible to appreciate the conflicts and disputes inside the groups of teachers, as well as the representations then constructed about the teaching profession. With that, the text proposes that the primary school teachers at the time of the Imperial Court participated actively in the process of construction of the teaching profession, becoming teachers through the public discussion and the collective production of professional identities. Identities that were always provisional, mobile and contradictory, but which functioned, nevertheless, as instruments of union around the definition of the idea of teaching as a mission of fundamental social and public significance.